Environmental Damage: Community Lawsuit Against The Government Over Industrial Business Licenses - Amiq, Bachrul; Borman, M. Syahrul; Taufik, Moh; Aranggraeni, Renda; Astuti, Pudji; Aimim-Tham, Sukanya; Aminah, Aminah (LAW REFORM, 2024)
Legal policies causing environmental damage raise questions about legal standing to file lawsuits with the State Administrative Court and its authority over business license disputes. This study examines the challenges and opportunities in implementing the authority of the state administrative court as a form of law enforcement on business licenses that impact environmental damage. This study uses the qualitative method NVivo12 Plus 12 by analyzing legal rules, journals, and online print media such as detik.com and kompas.com. The research focuses on the approach of laws and regulations related to the environment and case studies based on Supreme Court decisions. The Administrative Court plays a role in receiving claims against government actions that harm citizens. One of them is the authority to adjudicate disputes over government actions related to environmental disputes. Community participation is essential to create a healthy environment and is used not only as a means to an end but also as an end. The right to a healthy climate encompasses the right to receive environmental information, participate in decision-making, and review challenging public decisions within the scope of access to justice.